Data Analytics of Mobile Serious Games: Applying Bayesian Data Analysis Methods - Heide Lukosch; Scott Cunningham (Serious Games Society, 2018)
Traditional teaching methods in the field of resuscitation training show some limitations, while teaching the right actions in critical situations could increase the number of people saved after a cardiac arrest. For our study, we developed a mobile game to support the transfer of theoretical knowledge on resuscitation.  The game has been tested at three schools of further education. A number of data has been collected from 171 players. To analyze this large data set from different sources and quality, different types of data modeling and analyses had to be applied. This approach showed its usefulness in analyzing the large set of data from different sources. It revealed some interesting findings, such as that female players outperformed the male ones, and that the game fostering informal, self-directed is equally efficient as the traditional formal learning method.